The Application Development of Online Rental Housing Based Android - Lahmudin Sipahutar; Nursyah Handayani (Institut Teknologi Bisnis AAS Indonesia, 2023)
The use of technology and information in the development of a business is very necessary in this day and age, if there is a touch of technology then the business or business can survive and grow for the better. While those who still survive with the manual system will be eroded by the advancement of technology itself, one example of digital business development is the use of digital information systems such as the Marketing of rental houses through the android platform we can promote rental houses in the Medan region, so this system exists rental house owners can market their rental houses through the developed system. This system offers facilities for rental house seekers to rent, as well as house owners, so it is easy to market rental houses so that they can be rented by rental house seekers. This information system provides a clear picture to the rental house seekers in choosing the house they see through the Android Platform according to the tastes and needs of their respective tenants.